Incidence of constrained condylar and hinged knee implants and mid- to long-term survivorship: a register-based study from the Nordic Arthroplasty Register Association (NARA) - Von Hintze, Jake; Ponkilainen, Ville; W-Dahl, Annette; Hailer, Nils P; Furnes, Ove; Fenstad, Anne M; Badawy, Mona; Pedersen, Alma B; Lindberg-Larsen, Martin; Niemeläinen, Mika J; Mäkelä, Keijo; Eskelinen, Antti (MJS Publishing, Medical Journals Sweden AB, 2025)
Background and purpose: In complex primary total knee arthroplasty (TKA), constrained condylar knee (CCK) or rotating hinge knee (RHK) designs may be required to provide stability or address bony deficiencies. We analyzed trends in incidence of these designs in primary TKA and evaluated the mid- to long-term survivorship of CCK and RHK in 4 Nordic countries.
Methods: From 2000 to 2017, 5,134 CCK and 2,515 RHK primary TKAs were identified from the NARA database. Kaplan-Meier (K-M) survival and flexible parametric survival model (FPSM) analyses were performed to estimate revision risk, expressed as hazard ratio (HR) with 95% confidence intervals (CI), with minimally stabilized (MS) TKA acting as the control group (n = 456,137).
Results: The incidence of CCK and RHK implants increased significantly in Finland, while it was moderate in Denmark, Norway, and Sweden. With revision for any reason as the endpoint the 15-year K-M cumulative revision risk for RHK was 13.6% (CI 10.4-16.7) and for CCK it was 11.3% (CI 9.1-13.5). Compared with MS TKA, the hazard ratio for revision was 2.1 (CI 1.8-2.3) for CCK and 2.5 (CI 2.1-2.8) for RHK. Periprosthetic joint infection (PJI) was the most common reason for revision, accounting for 44% of CCK and 47% of RHK cases. After excluding revisions for PJI, the hazard ratio remained high for both designs, at 1.5 (CI 1.3-1.7) for CCK and 1.6 (CI 1.3-2.0) for RHK compared with MS.
Conclusion: The incidence of CCK and RHK increased during the study period. Both designs showed consistent 15-year revision risks of 11-14%, with no major differences between them. The higher revision risk compared with MS TKAs may reflect the complexity of the surgeries.